A taxonomic study on Themus (Telephorops) davidis species-group (Coleoptera, Cantharidae), with description of a new species from China - Yang, Yuxia; Zong, Le; Yang, Xingke; Liu, Haoyu (Zootaxa, 2019)
Themus (Telephorops) davidis species-group is redefined and we present a catalogue, identification key and distribution map for this group. Some previously known species are redescribed and we provide new illustrations of female internal genitalia, abdominal sternite VIII and/or aedeagus. Further, we report new distribution data. A new species, Themus (Telephorops) hainanus sp. nov. from China (Hainan) is described, and Themus (Telephorops) birmanicus Wittmer, 1983 is recorded from China for the first time.